Aura Budaya dalam Polykria - Junaidi, Alip Supar; Toekio, Soegeng (KEMADHA, 2011)
When the mass emotions appear to be part of the social dynamics are very different in scale, appear various opinions. There is a kind of pressure and sudden action, when life disturbed by the policies and the ease with which it is not considered correlative. Problems and action seemed to come simultaneously into clumps in the act. Among the many problems that must be faced, whether they are positive or negative, seems to never go completely dibincangkan.While men have always regarded as a maker-made; initiators, actors, even users of natural resources is very greedy; often get attitude pros and cons. Another phenomenon; form reclamasi action, such reforestation or conservation plan burst like the scale of urgency. This side was the tendency of trace some aspects that characterized the presence of a work of art that cares for the environment. A moment comes which depart from the vigorous performance of environmental information and scroll to the art.One might define good and evil, right and wrong or something more leads to ambivalent. Ambiguous condition was apparently also implied the treasures of art, where the conventional structure is confronted with a moderate reform. Artistic treasures are faced with two options open areas. Thats all fine. However the choice should remain grounded in the wisdom that leads to the front and opened the optimism in entering the global competition.